Deutsche und Italiener in Südtirol - Dörrenhaus, Fritz (ERDKUNDE, 1953)
Preface of the editor: There are few areas where investigations in political geography can be based on such sound foundations as is possible in South-Tyrol. Here two ethnic groups, differing in their social structure and also to a great extent in their economic outlook, have for over a millenium given rise to two distinct cultural landscapes. During the past decades, as a consequence of changes in State and administrative boundaries, they have been affected by powerful political and economic forces. The statistical data which allow a precise evaluation of these forces remained unpublished during the turbulent period of the recent war and were consequently not available for scientific investigations. The elections of 1952 gave rise on both sides of the Alps to newspaper campaigns in which partisan zeal threatened to obscure the actual facts from the public. The following paper, whose author is intimately acquainted with the area, attempts to display in an objective and scientific manner the historical and geographical data and to arrive at valid conclusions by drawing a comparison between the results of last year's elections and earlier statistical surveys. Of these the census data from 1910 to 1939, as well as the figures of the migration of the South- Tyrol Germans and Ladins which occured during the facist-national socialist period, have by now become available. With the publication of this general survey we hope to perform a useful service to geographers and also to students of the political sciences.